To find the equation in slope-intercept form \( y = mx + b \), we need to determine the slope \( m \) and the y-intercept \( b \).
From the data provided:
- At \( x = 0 \), \( y = 132 \)
- At \( x = 1 \), \( y = 165 \)
- At \( x = 2 \), \( y = 198 \)
- At \( x = 3 \), \( y = 231 \)
First, we can find the slope \( m \) by examining the change in \( y \) over the change in \( x \).
From \( x = 0 \) to \( x = 1 \):
- Change in \( y = 165 - 132 = 33 \)
- Change in \( x = 1 - 0 = 1 \)
Thus, the slope \( m \) is: \[ m = \frac{33}{1} = 33 \]
Now, we already know the y-intercept \( b \) from the data at \( x = 0 \): \[ b = 132 \]
Putting it all together, the equation in slope-intercept form is: \[ y = 33x + 132 \]
So, the correct expressions to complete the equation are: \[ y = 33x + 132 \]